Cover Feature: Wide‐Temperature Flexible Supercapacitor from an Organohydrogel Electrolyte and Its Combined Electrode (Chem. Eur. J. 25/2023). Issue 25 (4th April 2023) - Qian, Yuzhen; Yu, Yang; Wu, Wenna; Fan, Qi; Chai, Chunxiao; Hao, Jingcheng
Abstract : A flexible supercapacitor that integrates a wide application temperature range, satisfactory electrochemical performance and mechanical properties was fabricated by using anti‐freezing and anti‐drying organohydrogels both as electrolyte and binder of the combined electrode. The H2 O molecules in the organohydrogel are fixed in the 3D polyacrylamide network through the hydrogen bond interaction of ethylene glycol and ionic hydration of LiCl, thus greatly limiting their crystallization or evaporation at extreme temperatures. More information can be found in the Research Article by J. Hao and co‐workers (DOI: 10.1002/chem.202300123 ).